Beyond Confidence: Rethinking the Role of Self-Efficacy in English Speaking Skills - Carolina, Fitri; Sengkey, Virginia Gabrella (Faculty of Education and Teacher Training of UIN Palopo, 2025)
The objective of this study was to examine the relationship between students’ self-efficacy and their speaking proficiency. This quantitative research employed a descriptive and correlational design. Data were collected from 85 ninth-grade students at SMP Advent UNKLAB. Descriptive mean analysis and the Pearson Product-Moment Correlation Coefficient were utilized to address the research questions. The results indicated that: (1) students’ self-efficacy was measured at a mean score of 3.93, reflecting a high level; (2) students’ speaking ability scored an average of 95.18, categorized as very good; (3) the correlation analysis yielded a p-value of 0.429 and an R-value of -0.156, demonstrating no significant relationship between self-efficacy and speaking ability. Consequently, given the absence of a significant correlation between these variables, further investigation into other factors that may potentially influence students’ speaking ability is recommended.